Peningkatan Pengetahuan Masyarakat tentang Pencegahan Hipertensi dan Diabetes Melitus melalui Kegiatan Penyuluhan Kesehatan - Zakiyyatur Rizqi Isbaiyyah; Ika Maulida Ismaul Nur Hidayah; Lailin Niskiyah Nur Romadhoni; Nova Dewi Anggraini; Vivi Puspita Wijaya; Afidah Feby Nur Hidayah; Sesti Anggi Fatmala; Bagus Hari Prasetya; Muhammad Tanwir Qulubuts Saqib Yasin; Hafid Nurdin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Hypertension and diabetes mellitus remain major persistent non-communicable health problems requiring prompt recognition, prevention, and control. Insufficient community awareness regarding disease triggers, preventive strategies, and routine health monitoring remains a key issue. Therefore, this community service program aimed to enhance knowledge on hypertension and diabetes mellitus prevention, promote early screening awareness, and foster healthier lifestyle behaviors among residents of Paloh Village, Paciran District, Lamongan Regency. Conducted in August 2026 at the Paloh Village Hall, the activity engaged 27 participants through interactive lectures, leaflets, discussion sessions, and basic health examinations covering blood pressure, random blood glucose, and uric acid. Evaluation through pre- and post-tests demonstrated a clear knowledge increase, with the average score rising from 84.44 to 94.81, representing a 10.37-point improvement or roughly 12.3%. Specifically, 12 participants achieved better results, 15 maintained their initial scores, and none showed lower outcomes. These findings indicate that combining interactive education with printed material effectively strengthens community understanding regarding hypertension and diabetes mellitus prevention, while reinforcing the vital importance of early screening and healthy living habits.